Abordagens sintéticas para a funcionalização de novas porfirinas - Barona Castaño, Juan Camilo (Universidade Federal de São Carlos, 2016)
Herein, we optimized some conditions in the synthesis of a β-octasubstitued porphyrin with electron withdrawing groups (1). This system was used to study the bromination of the meso position aiming at subsequent cross-coupling reactions and meso-functionalization of these porphyrin systems (Scheme 3). The main goal was to obtain porphyrin derivatives with modulations in the UV-visible spectra with potential application as photosensitizers for photodynamic therapy treatments (PDT). We found better conditions for the preparation of the porphyrin 1 changing the formaldehyde precursor from trioxane to dimethoxymethane, and reducing the time of second step in the reaction (oxidation of the porphyrinogen). The yield was increased to 13%. After the optimization of 1, different bromination methodologies were tested in order to obtain the meso-bromoporphyrins 2 or 3; but unsuccessfully. In this perspective, we also proposed the synthesis of β-fused porphyrins with imide moieties (Scheme 4), being the functionalized pyrrole 8 the starting material. Porphyrins 9 and 11 might be alternatives for the preparation of new substituted derivatives via cross-coupling reactions, leading to compounds with different photophysical properties. The synthesis of porphyrin 9 was not succeeded by the approaches adopted here, showing only complex mixtures or total degradation of 8. Furthermore, experiments for the formation of dipyrrolmethane 10 were made without any success, precluding the construction of the porphyrin 11. Certain intermediates of interest could be isolated with relative success, and future explorations will be considered.
Keywords: Porfirinas; Meso-bromações; Dioxopirroloporfirinas; Anéis fundidos; Deslocamentos batocrômicos; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA